Students’ Difficulties In Understanding English Songs - Nurul Azizah Ria Kusrini (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2017)
This paper reports the result of a study which aims to argue the previous studies which report that listening through song can help the students to improve the listening comprehension. Listening is one of four integrated skills of learning English which become the most difficult skill for the students. This paper investigates the students’ difficulties in doing listening activity by using song. The students here represent the students of Junior High school, especially private school in remote area. The problems which are mostly and commonly faced by the students while listening are explained further in this paper. As the result, the researcher analyzes the problems may impede the students’ to do the exercises well. Moreover, this paper also gives suggestion which may help the teacher to overcome the students’ problem.